2017
DOI: 10.3892/mmr.2017.6848
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2-Ang (1–7)-Mas receptor axis attenuates cardiac remodeling and fibrosis in post-myocardial infarction

Abstract: Myocardial remodeling serves an important role in the pathophysiology of coronary heart disease. The angiotensin-converting enzyme (ACE)2-angiotensin-(1–7) [Ang (1–7)]-Mas receptor (MasR) axis is a key regulator in myocardial remodeling and development of heart failure. To investigate how ACE2-Ang-(1–7)-MasR axis function on myocardial remodeling and cardiac fibrosis in post-myocardial infarction (MI), male Sprague-Dawley rats (weight, 200±20 g) were used to establish the model of myocardial infarction by liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 38 publications
(104 reference statements)
2
44
0
3
Order By: Relevance
“…As is mentioned above, Ang-(1-7) and Ang-(1-9) have been proposed to be important mediators in cardioprotection [51]. A series of studies demonstrated that both plasma and myocardial tissue levels of Ang-(1-7) significantly increased in myocardial infarction [41,52]. In contrast, another study indicated that the circulating levels of Ang-(1-9), but not Ang-(1-7) levels, increased 1 week after myocardial infarction [38].…”
Section: Discussionmentioning
confidence: 96%
“…As is mentioned above, Ang-(1-7) and Ang-(1-9) have been proposed to be important mediators in cardioprotection [51]. A series of studies demonstrated that both plasma and myocardial tissue levels of Ang-(1-7) significantly increased in myocardial infarction [41,52]. In contrast, another study indicated that the circulating levels of Ang-(1-9), but not Ang-(1-7) levels, increased 1 week after myocardial infarction [38].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study in the same murine model demonstrated that treatment with olmesartan or telmisartan increased both cardiac ACE2 mRNA and protein expression while augmenting plasma Ang 1-7/Ang II ratios resulting in improved cardiac function and alleviated collagen disposition [40]. These experiments suggest that both ACE inhibitors and ARBs variably upregulated ACE2 expression [50]. ARBs inhibit binding of Ang II to AT1 receptor, permitting circulating Ang II to be shunted to ACE2 for conversion to Ang1-7.…”
Section: Ace2 Regulation and Cardiovascular Diseasementioning
confidence: 92%
“…RAAS is also up-regulated in diabetes leading to activation of AngII pathway and subsequently inflammation, increased oxidative stress, cell proliferation as well as apoptosis, and fibrosis which contribute to cardiac remodeling and atherosclerosis. While, ACE2 improves cardiac function by preventing myocardial fibrosis, reducing remodeling and the development of left ventricular hypertrophy as well as pressure-overload-induced heart failure [21].Therefore, RAAS inhibition by ACE inhibitors and angiotensin II receptor blockers has been recommended as the first line therapy in CVD in people with diabetes by lowering target-organ damageas well…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%